Dephosphorylation of the RNA sensors RIG-I and MDA5 by the phosphatase PP1 is essential for innate immune signaling - Wies, Effi (2013)
RIG-I and MDA5 have emerged as key cytosolic sensors for the detection of RNA viruses, leading to antiviral interferon (IFN) production. Recent studies highlighted the importance of posttranslational modification for controlling RIG-I antiviral activity. However, the regulation of MDA5 signal-transducing ability remains unclear. Here we show that MDA5 signaling activity is regulated by a dynamic balance between phosphorylation and dephosphorylation of its CARD domains. Employing a phosphatome RNAi screen, we identified PP1α and PP1γ as primary phosphatases responsible for MDA5 and RIG-I dephosphorylation, leading to their activation. Silencing of PP1α and PP1γ enhanced RIG-I and MDA5 CARD phosphorylation and reduced antiviral IFN-β production. PP1α and PP1γ depleted cells were impaired in their ability to induce interferon-stimulated gene expression, which resulted in enhanced RNA virus replication. This work identifies PP1α and PP1γ as regulators of antiviral innate immune responses to various RNA viruses, including influenza virus, paramyxovirus, dengue virus and picornavirus.